A new microspore embryogenesis system under low temperature which mimics zygotic embryogenesis initials, expresses auxin and efficiently regenerates doubled-haploid plants in Brassica napus - Prem Deepak; Solís María-Teresa; Bárány Ivett; Rodríguez-Sanz Héctor; Risueño María C; Testillano Pilar S (BMC Plant Biology, 2012)
Abstract Background Microspore embryogenesis represents a unique system of single cell reprogramming in plants wherein a highly specialized cell, the microspore, by specific stress treatment, switches its fate towards an embryogenesis pathway. In Brassica napus, a model species for this phenomenon, incubation of isolated microspores at 32°C is considered to be a pre-requisite for embryogenesis induction. Results We have developed a new in vitro system at lower temperature (18°C) to efficiently induce microspore embryogenesis throughout two different developmental pathways: one involving the formation of suspensor-like structures (52.4%) and another producing multicellular embryos without suspensor (13.1%); additionally, a small proportion of non-responsive microspores followed a gametophytic-like development (34.4%) leading to mature pollen. The suspensor-like pathway followed at 18°C involved the establishment of asymmetric identities from the first microspore division and an early polarity leading to different cell fates, suspensor and embryo development, which were formed by cells with different organizations and endogenous auxin distribution, similar to zygotic embryogenesis. In addition, a new strategy for germination of microspore derived embryos was developed for achieving more than 90% conversion of embryos to plantlets, with a predominance of spontaneous doubled haploids plants. Conclusion The present work reveals a novel mechanism for efficient microspore embryogenesis induction in B. napus using continuous low temperature treatment. Results indicated that low temperature applied for longer periods favours an embryogenesis pathway whose first division originates asymmetric cell identities, early polarity establishment and the formation of suspensor-like structures, mimicking zygotic embryogenesis. This new in vitro system provides a convenient tool to analyze in situ the mechanisms underlying different developmental pathways during the microspore reprogramming, breaking or not the cellular symmetry, the establishment of polarity and the developmental embryo patterning, which further produce mature embryos and plants.